Development and Single Laboratory Evaluation of a Refined and specific Real-time PCR Detection Method, Using Mitochondrial Primers (Mit1C), for the Detection of Cyclospora cayetanensis in Produce - Kannan V. Balan; Mark Mammel; David Lipman; Uma Babu; Lisa M. Harrison; Sonia Almeria; Mauricio Durigan; Susan R. Leonard; Hyein Jang; Solomon Gebru; John Grocholl; Socrates Trujillo; et al. (Journal of Food Protection, 2023)
Regulatory methods for detection of the foodborne protozoan parasite Cyclospora cayetanensis must be specific and sensitive. To that end, we designed and evaluated (in a single laboratory validation) a novel and improved primer/probe combination (Mit1C) for real-time PCR detection of C. cayetanensis in produce. The newly developed primer/probe combination targets a conserved region of the mitochondrial genome of C. cayetanensis that varies in other closely related organisms. The primer/probe combination was evaluated both in silico and using several real-time PCR kits and polymerases against an inclusivity/exclusivity panel comprised of a variety of C. cayetanensis oocysts, as well as DNA from other related Cyclospora spp. and closely related parasites. The new primer/probe combination amplified only C. cayetanensis, thus demonstrating specificity. Sensitivity was evaluated by artificially contaminating cilantro, raspberries, and romaine lettuce with variable numbers (200 and 5) of C. cayetanensis oocysts. As few as 5 oocysts were detected in 75%, 67.7%, and 50% of the spiked produce samples (cilantro, raspberries, and romaine lettuce), respectively, all uninoculated samples and no-template real-time PCR controls were negative. The improved primer/probe combination should prove an effective analytical tool for the specific detection of C. cayetanensis in produce.